Meningkatkan Akurasi dan Profesionalisme Pengelolaan Zakat melalui Pelatihan Penggunaan Kalkulator Zakat kepada Calon Amil Zakat - Wahab, Abdul; Widyastuti, Aulia Nur; Arashy, Adil Cahya; Ghany, Mochamad Abdul; Ali, Ilzamna Kamila (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service aims to increase accuracy and professionalism in zakat management through training on the use of zakat calculators for prospective zakat recipients. The main objective is to provide an in-depth understanding of zakat calculations, introduce zakat calculator technology, and improve prospective amil's skills in managing zakat funds more efficiently. The service method involves holding interactive training, group discussions, and simulating the use of a zakat calculator. The results of the service include increasing the understanding of prospective amil regarding zakat law, their ability to use zakat calculators effectively, and their professionalism in involving the community in managing zakat funds. Through this approach, it is hoped that prospective amil will become more competent and confident in managing zakat, ensuring a more targeted distribution of zakat funds, and supporting the growth and welfare of the beneficiary community.